Surgical portosystemic shunts versus devascularisation procedures for prevention of variceal rebleeding due to hepatosplenic schistosomiasis - Ede, Chikwendu Jeffrey (My University, 2017)
Background: Surgical interventions such as shunts and devascularisation procedures are effective therapies to prevent variceal rebleeding in people with hepatosplenic schistosomiasis. As this disease is prevalent in low income countries, the impact of eco-social factors result in poor compliance with nonsurgical therapies that require repeated sessions and long-term follow-up. Objectives: To determine whether surgical portosystemic shunts have better outcomes compared with oesophagogastric devascularisation procedures in the prevention of variceal rebleeding due to schistosomal portal hypertension (SPH). Methodology: This meta-analysis was conducted using standards expected by The Cochrane Collaboration. All randomised clinical trials comparing surgical portosystemic shunts with oesophagogastric devascularisation with or without splenectomy in the prevention of variceal rebleeding due to hepatosplenic schistosomiasis were selected. The risks of bias were assessed according to domains and risk of random errors with Trial Sequential Analysis. The quality of evidence was assessed using the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) Working Group approach. Results: Two trials met the inclusion criteria of this review and were selected. An analysis of 115 participants, 57 who received distal splenorenal shunt (DSRS) and 58 who received devascularisation procedure is presented. The trials were assessed at high risk of bias. There is no difference in overall mortality between DSRS versus devascularisation, risk ratio (RR) is 1.40, (95% confidence interval (CI) 0.32 to 6.15), downgraded to very low quality due to overall risk of bias, imprecision and publication bias. Variceal rebleeding following devascularisation is statistically significant higher than after DSRS (RR is 0.23, 95% CI 0.05 to 1.01), very low quality evidence due to bias, imprecision, and publication bias. The number of participants needed to treat with DSRS to achieve benefit (NNTB) is 8. Serious adverse events reported as procedure specific include: portal vein thrombosis, haemolysis, ascites and shunt dysfunction. There was no report on quality of life. DSRS is associated with a statistically significant higher post procedure encephalopathy (RR 8.10, 95% CI 1.04 to 62.83), downgraded to very low quality due to overall risk of bias, imprecision, and publication bias. Trial sequential analysis shows no strong evidence to accept or reject the difference in variceal rebleeding and encephalopathy rate for both interventions because of bias and inadequate sample size. Outcomes of proximal splenorenal shunt (PSRS) compared to devascularisation were reported by a single trial, therefore no meta-analysis was computed for this comparison, nor subgroup of PSRS compared to DSRS. Conclusion: Available evidence seems to suggest that DSRS is better than devascularisation for the prevention of variceal rebleeding due to hepatosplenic schistosomiasis, but this is at the cost of significant encephalopathy. The review authors are cautious to make this conclusion because overall evidence is very low quality and only few trials with small sample size are available. Further randomised clinical trials with adequate sample size and good methodological quality are needed.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in Surgery Johannesburg, 2017
Keywords: Portosystemic Schistosomiasis